Youla Parameterization Based Control Performance Degradation Online Recovery of Single Inverter Control Systems in Microgrids: a PnP Approach. Issue 2 (2020) - Liu, Y.; Hu, C.; Lu, H.; Ding, S.X.; Li, L.; Peng, X.; Wang, Y.
Abstract: In an inverter control system of smart microgrids, the control performance degradation due to load fluctuations, unbalanced loads and other factors, is one of the considerable factors affecting the output power quality. In this paper, a plug-and-play (PnP) technology based on Youla parameterization is proposed to achieve system performance recovery without modifying the existing controller. By 'plugging-in' a residual generator and a compensator, a dynamic feed-back of residual signals is embedded into the original inverter control system. In order to realize PnP, an online parameter estimation scheme of the compensator is developed. Finally, an inverter control system is applied to show the effectiveness of the proposed approach.